A Facile Synthetic Route to a New SHG Material with Two Types of Parallel π-Conjugated Planar Triangular Units - Song, Jun-Ling; Hu, Chun-Li; Xu, Xiang; Kong, Fang; Mao, Jiang-Gao (Angewandte Chemie International Edition, 2015)
A new SHG material, namely, Pb2(BO3)(NO3), which contains parallel π‐conjugated nitrate and borate anions, was obtained through a facile hydrothermal reaction by using Pb(NO3)2 and Mg(BO2)2⋅H2O as starting materials. Its structure contains honeycomb [Pb2(BO3)]∞ layers with noncoordination [NO3]− anions located at the interlayer space. Pb2(BO3)(NO3) shows a remarkable strong SHG response of approximately 9.0 times that of potassium dihydrogen phosphate (KDP) and the material is also phase‐matchable. The large SHG coefficient of Pb2(BO3)(NO3) arises from the synergistic effect of the stereoactive lone pairs on Pb2+ cations and parallel alignment of π‐conjugated BO3 and NO3 units. Based on its unique properties, Pb2(BO3)(NO3) may have great potential as a high performance NLO material in photonic applications. Pb2(BO3)(NO3) is a new second‐harmonic generation (SHG) material that contains parallel π‐conjugated nitrate and borate anions. It was obtained through a facile hydrothermal reaction, shows a remarkable strong SHG response of about 9.0 times that of potassium dihydrogen phosphate (KDP), and is phase‐matchable.